Site of pregnancy obstetrician’s dilemma - Chandra, Rudrika; Singh, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
A 28-yr-old P2L2 lady, with history of two previous caesarean deliveries and tubal ligation, presented at 6weeks of amenorrhea with pain lower abdomen. The operative notes from her previous caesarean section stated that she had a unicornuate uterus without a rudimentary horn (ASRM Class II D Mullerian anomaly)5 and only right fallopian tube was visualised, which was ligated by Parkland’s method. On workup, she had a positive urine pregnancy test and ultrasound showed a left adnexal mass without any evidence of intraperitoneal collection, possibly an unruptured left ovarian ectopic pregnancy secondary to failed tubal ligation. Further investigation by MRI revealed an entirely new finding. The suspicious left adnexal mass was the left horn of bicornuate uterus which had an intrauterine gestational sac. Hence, her revised diagnosis was G3P2L2, post LSCS, bicornuate uterus (ASRM class IV B) with 6 weeks of intrauterine left horn pregnancy following failed tubal ligation. She underwent a medical followed by surgical evacuation of intrauterine pregnancy as patient was unwilling to continue the pregnancy. This case highlights the importance of a comprehensive evaluation, whenever a lady is diagnosed with a Mullerian anomaly, in order to correctly classify the patient and identify associated anomalies of urogenital tract which would avoid such erroneous diagnosis of site of pregnancy as illustrated in our case.